2020
DOI: 10.1371/journal.pone.0230640
|View full text |Cite
|
Sign up to set email alerts
|

HPV genotypic spectrum in Jilin province, China, where non-vaccine-covered HPV53 and 51 are prevalent, exhibits a bimodal age-specific pattern

Abstract: Background Human papillomavirus (HPV), the most common sexually transmitted disease, is involved in a series of other diseases. The persistent infection of high-risk HPVs (HR-HPVs) is considered to be the causative agent of cervical cancer, and it is related to noncervical cancers. The present study aims to estimate the HPV prevalence and genotype distribution in Jilin province, China, to guide HPV-related cervical cancer screening and HPV vaccination. Methods From October 2017 to September 2019, 21,282 sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 38 publications
9
18
0
Order By: Relevance
“…And in spite of low percentage of positive hr HPV in our samples, our study revealed that there was increase in p ercent ag e o f posit ive h rHPV wit h in crease sev erity o f cyto log ical ab no rmalit y. And this approved by many other study like Turkish study (24) and Chinese study (25) .…”
Section: Discussionsupporting
confidence: 53%
“…And in spite of low percentage of positive hr HPV in our samples, our study revealed that there was increase in p ercent ag e o f posit ive h rHPV wit h in crease sev erity o f cyto log ical ab no rmalit y. And this approved by many other study like Turkish study (24) and Chinese study (25) .…”
Section: Discussionsupporting
confidence: 53%
“…The overall HPV-positive detection rate in normal women ranges from 7.2% (Malaysia) to 41.7% (Hong Kong). The HPV genotypes commonly detected in these regions are HPV16, 18, 52, 58, 31, 33, 35, 39, 45, 51, 56, 59, 68, 6, 11, 42, 43, and 81 [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ].…”
Section: Hpv Genotype Distribution In East Southeast and South Asiamentioning
confidence: 99%
“…The overall HPV-positive detection rate in normal women ranges from 7.2% (Malaysia) to 41.7% (Hong Kong). The HPV genotypes commonly detected in these regions are HPV16, 18,52,58,31,33,35,39,45,51,56,59,68,6,11,42,43, and 81 .…”
Section: Hpv Genotype Distribution In East Southeast and South Asiamentioning
confidence: 99%
See 2 more Smart Citations